2021
DOI: 10.3389/fimmu.2021.593255
|View full text |Cite
|
Sign up to set email alerts
|

Putting Proteomics Into Immunotherapy for Glioblastoma

Abstract: In glioblastoma, the most aggressive brain cancer, a complex microenvironment of heterogeneity and immunosuppression, are considerable hurdles to classify the subtypes and promote treatment progression. Treatments for glioblastoma are similar to standard therapies for many other cancers and do not effectively prolong the survival of patients, due to the unique location and heterogeneous characteristics of glioblastoma. Immunotherapy has shown a promising effect for many other tumors, but its application for gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 105 publications
(105 reference statements)
0
14
0
Order By: Relevance
“…While the genetic alterations in GBM are highly informative, it is vital to gain as deep an understanding of the proteomic changes, as these are the functional consequences of modifications to the genome. For this purpose, mass spectrometry is a valuable tool in the study of GBM, both in basic research and the identification of biomarkers. , Increasingly, mass spectrometry is poised to complement or eventually replace traditional diagnostic methods of GBM presence, stage, and subtype . The high sensitivity of mass spectrometry and its ability to investigate multiple protein biomarkers simultaneously has shown it to be a promising diagnostic tool in various biological samples, including biopsy tissue, cerebrospinal fluid (CSF), blood plasma, urine, extracellular vesicles, and even fluid from cavitating ultrasound aspirators used during tumor removal. Many studies have investigated alterations in protein expression in GBM and several papers have reviewed potential GBM biomarkers in tumor tissue, CSF, plasma, and serum. However, there is no recent comprehensive review of the literature that determines which proteins and therefore which biological processes are commonly differentially regulated in GBM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the genetic alterations in GBM are highly informative, it is vital to gain as deep an understanding of the proteomic changes, as these are the functional consequences of modifications to the genome. For this purpose, mass spectrometry is a valuable tool in the study of GBM, both in basic research and the identification of biomarkers. , Increasingly, mass spectrometry is poised to complement or eventually replace traditional diagnostic methods of GBM presence, stage, and subtype . The high sensitivity of mass spectrometry and its ability to investigate multiple protein biomarkers simultaneously has shown it to be a promising diagnostic tool in various biological samples, including biopsy tissue, cerebrospinal fluid (CSF), blood plasma, urine, extracellular vesicles, and even fluid from cavitating ultrasound aspirators used during tumor removal. Many studies have investigated alterations in protein expression in GBM and several papers have reviewed potential GBM biomarkers in tumor tissue, CSF, plasma, and serum. However, there is no recent comprehensive review of the literature that determines which proteins and therefore which biological processes are commonly differentially regulated in GBM.…”
Section: Introductionmentioning
confidence: 99%
“…These advances arise from increased mass accuracy and resolution, as well as gains in instrument sensitivity as a result of technological advancements such as the growth in the use of hybrid instruments, which allow for methods of ion fractionation and storage and greater scan rates . For example, constantly developing technologies such as the Orbitrap developed by Thermo Fisher increase the number of peptides that can be detected simultaneously. , This results in increased coverage of individual proteins, enabling detection of lower abundance proteins and thus increasing coverage of the proteome as a whole. , Furthermore, quantitative analysis has been refined with the development of isobaric tags for relative and absolute quantification (iTRAQ), tandem mass tags (TMT), and dimethyl labeling. Indeed, proteomic technology and analysis software has now been developed to allow simpler and cheaper label-free quantification . These technical improvements have opened up proteomics as a valuable and sensitive tool for a number of clinical applications …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer immunotherapy is an important method of treating cancer, in which the patients' own immune system is used to fight tumors (20), thus it has been widely used in the treatment of a variety of tumors (21). Cancer immunotherapy urgently needs biomarkers to accurately predict clinical response, and it has been applied to glioma (22,23). Immune infiltration analysis found that CMTM3 is highly correlated with a variety of immune cells, such as B cell, CD8 + T cell, CD4 + T cell, macrophage, neutrophil, and dendritic cell.…”
Section: Discussionmentioning
confidence: 99%
“…Although transcriptomics provides a more dynamic view of a cancer cell and however, mRNAs are now considered to be a poor predictor of protein levels. Cancer proteomics analyses are now emerging as a powerful technique to predict the therapeutic response in cancer patients particularly for immunotherapy (Chen et al, 2021 ). By integrating transcriptome and proteome Andrieux et al showed that the mRNA-to-protein correlation analysis can serve as a unique approach to identify the pathways prioritized by the tumor cells at different clinical stages.…”
mentioning
confidence: 99%